(3cJGH aj GdWHs
(3ChdgG (B:s
(3GdMeO ddg GdTGaj aj GdCeQGV hGdYdd , GdZGaQ HaVdg dLejY GdBKGe hGdRdd aEf GdadGSaI GdbOeGA McehG HCf GdcGed GdaGVd hGdehUha HfgGjI GdYbd ef JcGedJ ajg s
(3BNQgG (B:s
(3hdSGf GdKhQ eLaakG, hHPQ GdHGRgQ fMhjg (B((3?(B) (3Qhei ef cd hGMO fUa OQge efg OQgekG hCJee s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B200 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdQHGW (B- (3GdeZQH (B((3O (B532) s
Keywords: (3GdWHs